A Study On The Compatibility Of "Passport To The World 2" Textbook For The Second Year Students Of Junior High School With School Based Curriculum - HANDAYANI , TRI (2012)
This research paper is mainly intended to find out whether the English textbook used for the second year students of Junior High School Passport to the World 2 develops the skills developed by School-based Curriculum. The writer employs descriptive qualitative method. In collecting the data, the writer used document as data source. The data were analyzed by these steps: (1) Presenting materials in the textbook and School-based Curriculum, (2) Comparing them, (3) Judging whether the data are compatible with indicators in School-based Curriculum or not, (4) Giving percentage, (5) Drawing conclusion and proposing suggestions. The result of analysis shows that the percentage of the compatibility of the skills developed in the textbook is 63,89% (Listening : 60%, Speaking: 61,53%, Reading: 66,67%, and Writing: 71,4 compatible with School-based Curriculum in developing skills. This research shows that the textbook entitled Passport to the World 2 is good materials to support teaching learning process especially in speaking, reading, and writing. The material of listening skill in the textbook is not adequate, so the listening teaching learning process need other materials to support the listening lesson. The result of study implies that the teacher should supply the textbook analyzed with other books which much better in order to achieve the goal of teaching English. The writer of the textbook should revise the textbook and add more text, and activities to increase the quality of the textbook.